Sustaining the Fabric of Time: Urban Heritage, Time Rupture, and Sustainable Development - Kaixuan Wang; Kalliopi Fouseki (Land)
This paper explores the concept of time rupture, i.e., the disruption of historical continuity caused by rapid urbanization, and its implications for urban heritage preservation, using Dongjiadu in Shanghai as a case study. Time rupture highlights the disconnection between modern development and cultural heritage, often diluting local identity and a sense of place. While it presents challenges to the continuity of urban heritage, it also creates opportunities to redefine historical narratives and enrich cultural meaning. By introducing a temporal framework, this study examines the dynamic interplay between heritage preservation and modernity, advocating for adaptive, context-sensitive strategies that move beyond static conservation methods. These strategies acknowledge the fragmented overlaps of urban timelines, ensuring that heritage sites remain vibrant, living components of urban environments. The Dongjiadu case illustrates two distinct categories of time rupture, underscoring the need for sustainable practices that harmonize cultural continuity with contemporary growth. The discussion emphasizes the importance of inclusive practices, community engagement, and the critical integration of technological advancements to address time rupture effectively. By incorporating a temporal perspective into heritage conservation, it is possible to bridge historical continuity and modern development, foster resilience in urban environments, and enable cities to adapt to rapid change while retaining their cultural essence. Ultimately, addressing time rupture through thoughtful, adaptive strategies ensures that urban heritage actively contributes to the sustainability and vitality of evolving cities.